(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate early postoperative outcomes of arteriovenous fistula surgery in patients with chronic kidney disease. Methods: A retrospective case series of 38 patients with end-stage chronic kidney disease undergoing arteriovenous fistula surgery at Kien Giang provincial General Hospital from December 2023 to February 2024. Study variables included clinical characteristics, Doppler ultrasound findings before and 1 month after surgery, success rate, and early complications. Results: The early success rate of arteriovenous fistula at 1 month was 81.6%. Early complications included graft occlusion (7.9%), steal syndrome (2.6%), and limb dystrophy (2.6%). The mean blood flow measured by Doppler ultrasound was 1011.6 ml/min. Conclusion: Early outcomes of arteriovenous fistula surgery at Kien Giang provincial General Hospital showed good initial results, but the complication rate remained significant. Improving preoperative assessment and strict management of risk factors are necessary to optimize treatment outcomes.